X-ray vs. NMR structure of N-terminal domain of δ-subunit of RNA polymerase - Demo, Gabriel; Papoušková, Veronika; Komárek, Jan; Kadeřávek, Pavel; Otrusinová, Olga; Srb, Pavel; Rabatinová, Alžbeta; Krásný, Libor; Zídek, Lukáš; Sklenář, Vladimír; Wimmerová, Michaela (Journal of structural biology, 2014)
The crystal structure of the N-terminal domain of the RNA polymerase δ subunit (Nδ) from Bacillus subtilis solved at a resolution of 2.0Å is compared with the NMR structure determined previously. The molecule crystallizes in the space group C222(1) with a dimer in the asymmetric unit. Importantly, the X-ray structure exhibits significant differences from the lowest energy NMR structure. In addition to the overall structure differences, structurally important β sheets found in the NMR structure are not present in the crystal structure. We systematically investigated the cause of the discrepancies between the NMR and X-ray structures of Nδ, addressing the pH dependence, presence of metal ions, and crystal packing forces. We convincingly showed that the crystal packing forces, together with the presence of Ni(2+) ions, are the main reason for such a difference. In summary, the study illustrates that the two structural approaches may give unequal results, which need to be interpreted with care to obtain reliable structural information in terms of biological relevance.
Keywords: DNA řízené RNA-polymerasy; konformace proteinů; sekvence aminokyselin; Bacillus subtilis; Nuclear Magnetic Resonance, Biomolecular; Protein Conformation; Crystallography, X-Ray; Protein Structure, Secondary; nukleární magnetická rezonance biomolekulární; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; DNA-Directed RNA Polymerases; Amino Acid Sequence; sekundární struktura proteinů; krystalografie rentgenová